Building a rich vocabulary of unfamiliar literary text items with students - An active approach to meaning, context, and dictionary - Valerija B. Janićijević; Мilena B. Mitrović; Bojan M. Marković (University of Belgrade, Teacher Education Faculty, 2024)
Unfamiliar literary text terms should, by different methodological approaches and methods, become a part of the students' vocabulary and enrich their languaculture. The goal of this pilot research was to examine the elements of a specifically designed teaching medium (the Dictionary) in literature classes where literary works are analyzed. The purpose of the dictionary was to provide a deeper understanding of the meaning and usage of the completely new words in the students' vocabulary, through various approaches to those words and their meaning. The test group consisted of 25 experimental group students and 16 control group students. The experimental group students used an additional teaching medium in analyzing the unfamiliar terms in their texts, while the control group students analyzed their terms in a regular, conventional way. It has been concluded that the new, unfamiliar terms introduced in the text analysis in literature classes should be given more (methodological) attention, by using various methods and teaching mediums in order for those words to be understood and later actively used by students.Using an additional teaching medium, the Dictionary, has proven to be a successful way of analyzing unknown words, good for memorizing their different meanings, as well as using the newly adopted terms and phrases depending on their context length (used in a sentence or a short story).